Electromechanical performances of dual system PDMS dielectric elastomer - Ahmad Farimin, Ahmad Osman; Ahmad Hafiz, Mohd Jamil; Shamsul, Zakaria (Institute of Electrical and Electronics Engineers Inc., 2022)
Polydimethylsiloxane (PDMS) based films, as one promising type of dielectric film, exhibit large deformation percentage and has good thermal tolerance. Despite significant mechanical performance, the drawback of PDMS dielectric elastomer (PDE) is that it has low relative permittivity. Several single systems like compositing hard filler or soft filler into the PDMS matrices is reported to enhance the relative permittivity to some extent however it also gives negative impact on other PDE parameters such as increasing Young's modulus and higher the risk of premature electrical breakdown. Thus, this paper presents the synthesis of dual system PDE that has two PDMS layers filled with high permittivity fillers. Then, the performance of the dual system is carefully investigated in terms of its breakdown strength, relative permittivity and Young's modulus. The results show that the dual system of TiO2/ Gly demonstrates the most significant improvement in all three dielectric film parameters all in all.